2020
DOI: 10.22541/au.159611470.05918049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The antagonistic effects and mechanisms of microRNA-26a action in hypertensive vascular remodeling

Abstract: Background and Purpose: Hypertensive vascular remodeling (VR) is responsible for end-organ damage and is the result of increased extracellular matrix accumulation and excessive vascular smooth muscle cell (VSMC) proliferation. MicroRNA-26a (miR-26a), a non-coding small RNA, is involved in multiple cardiovascular diseases. We aimed to validate the effect and mechanisms of miR-26a in hypertensive VR. Experimental Approach: Spontaneously hypertensive rats (SHRs) were injected intravenously with recombinant adeno-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This study indicated that vascular remodeling (VR) due to hypertension leads to alteration in vascular structure and function. This study showed the protective role of microRNAs (MiR-26a) in VR, which could be investigated as a promising target in the therapy of hypertensive VR [ 51 ].…”
Section: Role Of Renin-angiotensin-aldosterone-system (Raas) In Hypertension and Target Organ Damagementioning
confidence: 99%
“…This study indicated that vascular remodeling (VR) due to hypertension leads to alteration in vascular structure and function. This study showed the protective role of microRNAs (MiR-26a) in VR, which could be investigated as a promising target in the therapy of hypertensive VR [ 51 ].…”
Section: Role Of Renin-angiotensin-aldosterone-system (Raas) In Hypertension and Target Organ Damagementioning
confidence: 99%